Characterization of HIV‐1 drug resistance among patients with failure of second‐line combined antiretroviral therapy in central Ethiopia. Issue 2 (7th October 2021) - Tufa, Tafese Beyene; Fuchs, Andre; Orth, Hans Martin; Lübke, Nadine; Knops, Elena; Heger, Eva; Jarso, Godana; Hurissa, Zewdu; Eggers, Yannik; Häussinger, Dieter; Luedde, Tom; Jensen, Björn‐Erik Ole; et al.
Abstract: Background: As a consequence of the improved availability of combined antiretroviral therapy (cART) in resource‐limited countries, an emergence of HIV drug resistance (HIVDR) has been observed. We assessed the prevalence and spectrum of HIVDR in patients with failure of second‐line cART at two HIV clinics in central Ethiopia. Methods: HIV drug resistance was analysed in HIV‐1‐infected patients with virological failure of second‐line cART using the geno2pheno application. Results: Among 714 patients receiving second‐line cART, 44 (6.2%) fulfilled the criteria for treatment failure and 37 were eligible for study inclusion. Median age was 42 years [interquartile range (IQR): 20–45] and 62.2% were male. At initiation of first‐line cART, 23 (62.2%) were WHO stage III, mean CD4 cell count was 170.6 (range: 16–496) cells/µL and median (IQR) HIV‐1 viral load was 30 220 (7963–82 598) copies/mL. Most common second‐line cART regimens at the time of failure were tenofovir disoproxil fumarate (TDF)‐lamivudine (3TC)‐ritonavir‐boosted atazanavir (ATV/r) (19/37, 51.4%) and zidovudine (ZDV)‐3TC‐ATV/r (9/37, 24.3%). Genotypic HIV‐1 resistance testing was successful in 35 (94.6%) participants. We found at least one resistance mutation in 80% of patients and 40% carried a protease inhibitor (PI)‐associated mutation. Most common mutations were M184V (57.1%), Y188C (25.7%), M46I/L (25.7%) and V82A/M (25.7%). High‐level resistance against the PI ATV (10/35, 28.6%) and lopinavir (LPV) (5/35, 14.3%) was reported. As expected, no resistance mutations conferring integrase inhibitor resistance were detected. Conclusions: We found a high prevalence of resistance mutations, also against PIs (40%), as the national standard second‐line cART components. Resistance testing before switching to second‐ or third‐line cART is warranted.